Developing helping skills : a step-by-step approach to competency - Chang, Valerie Nash; Decker, Carol L.; Scott, Sheryn Thompson (Boston: Cengage, 2018)
"Chang, Decker, and Scott's multilayered teaching and learning system provides a creative blend of learning methods and clear presentation of topics to help students think like practitioners and apply foundational skills to real-world practice. Students first read about professional practice and the skills required to work effectively with clients. Next, they reflect on and write about the ideas in the text by completing homework exercises that follow each new concept. The book also includes a case, presented one section at a time, with questions that engage students in learning how to think like professionals. Role-playing in practice interviews promotes skill development, and simple evaluation tools allow for ongoing evaluation of competencies."--Publisher's website.
Section 1: Foundation -- 1. Understanding yourself and others ; 2. Ways of understanding and perceiving self and others ; 3. Values, ethics, and legal obligations ; 4. Professionalism and professional relationships -- Section 2: Building professional relationships -- 5. Developing working relationships ; 6. Foundational interpersonal skills ; 7. Beginning and ending a meeting ; 8. Demonstrating active listening -- Section 3. Exploring and assessing with clients -- 9. Using questions ; 10. Exploring and discovering ; 11. Assessing readiness and motivation -- Section 4: Defining the focus -- 12. Identifying key problems or challenges ; Establishing goals -- Section 5: Doing, evaluating, and ending the work -- Taking action ; Evaluating and ending professional relationships.
Includes bibliographical references (pages 303-317) and index.
Keywords: Counseling; Helping behavior; Counseling; Helping behavior